2011
DOI: 10.1542/peds.2011-0480e
|View full text |Cite
|
Sign up to set email alerts
|

Patient Engagement and Attrition in Pediatric Obesity Clinics and Programs: Results and Recommendations

Abstract: Pediatric tertiary care institutions are well positioned to provide multidisciplinary, intensive interventions for pediatric obesity known as stage 3 treatment. One contributor to the difficulty in administering this treatment is the high rate of patient attrition. Little is known about the practices used by pediatric weight-management clinics and groupbased programs to minimize attrition. Hospital members and nonmembers of FOCUS on a Fitter Future were surveyed on the methods used to engage and retain obese c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
92
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 15 publications
8
92
1
Order By: Relevance
“…The results of this study are consistent with other reports of parental preferences and perceived barriers to health behavior change, 15,16,26 and additionally provide insight into the factors that may enable versus hinder participation in behavioral weight loss treatments in the population of youth who are high weight and treated with antipsychotic medications. First, we found that families reported a high level of motivation to participate in a weight loss program, but only a minority of families had completed treatment recommended by a healthcare provider.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The results of this study are consistent with other reports of parental preferences and perceived barriers to health behavior change, 15,16,26 and additionally provide insight into the factors that may enable versus hinder participation in behavioral weight loss treatments in the population of youth who are high weight and treated with antipsychotic medications. First, we found that families reported a high level of motivation to participate in a weight loss program, but only a minority of families had completed treatment recommended by a healthcare provider.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, many caregivers noted pragmatic barriers to participation, such as appointment availability and time constraints, as well as the time and difficulty related to the homework involved in most behavioral weight loss interventions (e.g., logging of food intake and PA). These results are similar to those reported in non-mentally ill obese pediatric populations, 15,26 and suggest that potential strategies to decrease pragmatic barriers to participation in the general population might also be useful in the population of obese youth with psychiatric conditions. These might include the use of telemedicine for remote access to providers and use of mobile device applications to simplify treatment-related homework.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…[4][5][6] Although effective for certain patients/ families, weight management clinics often are not feasible because of barriers associated with accessibility, transportation, and cost. [7][8][9] Clearly, novel approaches are necessary to enhance interventions in primary care settings, extending the impact of weight management clinics and thereby avoiding progression to tertiary care referrals. Interventions included usual care, MI from a PCP (4 sessions), and MI from both a PCP (4 sessions) and an RD (6 sessions).…”
mentioning
confidence: 99%